Determinants of tuberculosis treatment failure in public health facilities of Jigjiga Town, Somali Regional State, Ethiopia: A multi-center case-control study - Nasir Tayib Nur; Yadeta Dessie; Samuel Demissie Darcho; Samrawit Berihun; Behailu Hawulte Ayele (Clinical Epidemiology and Global Health)
Background: Early identification of determinants of tuberculosis treatment failure is crucial in resource-limited developing countries. Tuberculosis treatment failure is one of the challenges to controlling tuberculosis. However, evidence on the factors contributing to tuberculosis treatment failure is limited. Therefore, this study aims to determine the factors contributing to tuberculosis treatment failure. Methods: A retrospective, unmatched case-control study design was conducted by recruiting 264 (53 cases and 211 controls) at public health facilities. Cases were patients with pulmonary tuberculosis with a tuberculosis treatment outcome registered as treatment failure. Controls were patients with pulmonary tuberculosis with tuberculosis treatment outcomes registered as cured and treatment completed during anti-tuberculosis treatment. Result: 264 records (53 cases and 211 controls) were included from tuberculosis registers. In the current study, determinants of tuberculosis treatment failure were being male (AOR = 4.06, 95 % CI: 1.65, 9.75), age 30–40 years (AOR = 0.24, 95 % CI: 0.10, 0.54), receiving directly observed therapy treatment (AOR = 3.94, 95 % CI: 1.63, 9.51), adherence to tuberculosis medication (AOR = 7.56, 95 % CI: 2.70, 20.78), being treated at a hospital (AOR = 11.89, 95 % CI: 3.80, 33.79), and being HIV positive (AOR = 4.783, 95 % CI: 1.46, 15.65). (Table 4) Conclusions: This study found that the rate of tuberculosis treatment failure among adult patients with pulmonary tuberculosis was relatively lower in Eastern Ethiopia. Targeted interventions should be implemented to address the identified risk factors, particularly among high-risk groups, to improve tuberculosis treatment outcomes throughout the treatment process.